5x-3(x-1)-7=2(x-2)

Simple and best practice solution for 5x-3(x-1)-7=2(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3(x-1)-7=2(x-2) equation:


Simplifying
5x + -3(x + -1) + -7 = 2(x + -2)

Reorder the terms:
5x + -3(-1 + x) + -7 = 2(x + -2)
5x + (-1 * -3 + x * -3) + -7 = 2(x + -2)
5x + (3 + -3x) + -7 = 2(x + -2)

Reorder the terms:
3 + -7 + 5x + -3x = 2(x + -2)

Combine like terms: 3 + -7 = -4
-4 + 5x + -3x = 2(x + -2)

Combine like terms: 5x + -3x = 2x
-4 + 2x = 2(x + -2)

Reorder the terms:
-4 + 2x = 2(-2 + x)
-4 + 2x = (-2 * 2 + x * 2)
-4 + 2x = (-4 + 2x)

Add '4' to each side of the equation.
-4 + 4 + 2x = -4 + 4 + 2x

Combine like terms: -4 + 4 = 0
0 + 2x = -4 + 4 + 2x
2x = -4 + 4 + 2x

Combine like terms: -4 + 4 = 0
2x = 0 + 2x
2x = 2x

Add '-2x' to each side of the equation.
2x + -2x = 2x + -2x

Combine like terms: 2x + -2x = 0
0 = 2x + -2x

Combine like terms: 2x + -2x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 4t+9+(2t+7)= | | -6=6+k | | -3(x-4)+7=-2x | | (4x^2-3x)(6x+5)=0 | | 3x-25=11x-5+2x | | 5(x-3)=2x+21 | | 5y+2x=25 | | 26+4y-4=16y-13-5y | | 3x-0.25y=-2 | | x+0.20(3)=0.60(x+3) | | 22x+8-24x=7-9 | | 6-(5p+3)=6[(5p-3)-(p-7)] | | -4x+16=-11x+10 | | 10x+9-9x=15 | | x=-14-3x | | -10+18=m-9 | | -15=5(3q-10) | | -3x-5=5+2x | | -3t-4=7 | | -8x+10=-x+80 | | 7x=-47 | | 3(6+8R)-3(R+2)= | | 4k^2+26k-36=0 | | -5=x-9 | | 4(x+8)=-4(x-16) | | -0.01x^2+0.92x=0 | | 5e+10=25 | | -6=n+2+7n | | 3x+2x+3+3x+2x+3=5x-3+5x-3+5x-3 | | x+4/2=5/2-x-1/5 | | -4=8w-12 | | 10x+7+3x=0 |

Equations solver categories